ADVANCING APPROACHES TO STRENGTHEN STUDENTS' PROFESSIONAL SKILLS IN THE DIGITAL ERA - Tadjiboyev Kamoldin Abdusadikovich, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract In  the  rapidly  evolving  digital  landscape,  the  development  of  students’ professional skills requires innovative and adaptive teaching approaches. This paper explores advanced methodologies that integrate digital tools and modern educational strategies  to  enhance  students’  readiness  for  the  workforce.  Emphasizing  blended learning, competency-based education, and technology-driven instruction, the study highlights how digitalization fosters personalized, interactive, and practical learning experiences. Additionally, it addresses challenges such as digital literacy gaps and the need  for  continuous  curriculum  adaptation.  By  leveraging  digital  advancements, educators  can  equip  students  with  the  essential  competencies  required  in  today’s professional environment.